Development and validation of ethnomathematics-based worksheets integrating Sundanese Pupuh for enhancing number pattern learning in Indonesian secondary schools - Pitri Aulia Aulia; Rani Sugiarni; Camilo Andrés Rodríguez-Nieto (Nashir Al-Kutub Indonesia, 2025)
This study addresses the persistent challenge of low mathematical performance among Indonesian secondary students, particularly in learning number patterns, by developing culturally responsive teaching materials. Although Indonesia’s PISA performance has improved, students remain below the OECD average, with prior studies highlighting difficulties in pattern recognition, symbolic representation, and generalization. To address this issue, the study bridges abstract mathematical concepts with students’ cultural contexts through the development of ethnomathematics-based student worksheets integrating Sundanese Pupuh, a traditional literary art form characterized by structured numerical patterns in syllable counts and line arrangements. The research employed a Research and Development approach using the 4D model (Define, Design, Develop, Disseminate). The worksheets were designed to explicitly connect the inherent mathematical structures of Pupuh—guru wilangan and guru lagu—with formal number pattern concepts in the eighth-grade mathematics curriculum. The development process included needs analysis, alignment with Indonesia’s Merdeka Curriculum, and analysis of student characteristics. Expert validation conducted by mathematics education lecturers and prospective teachers resulted in a combined validity score of 90%, categorized as very valid. Practicality testing with eighth-grade students yielded a score of 92.6%, indicating high usability. This study contributes to mathematics education in three key ways: (1) introducing a novel pedagogical use of indigenous cultural heritage to support abstract mathematical learning, (2) providing empirically validated culturally responsive worksheets that address specific difficulties in number pattern learning, and (3) offering a replicable framework for integrating ethnomathematics into formal curricula. The findings suggest that culturally grounded instruction can enhance student engagement and conceptual understanding, with potential application to other cultural contexts.